Monitoring of AC Traction Substation Equipment - Kyrylenko, O.V.; Stognii, B.S.; Sopel, M.F.; Tankevych, S.Ye. (Science and Innovation, 2024)
The basic results of R&D project on the design of a system for monitoring equipment of traction substations of railway transport implemented in the Institute of Electrodynamics of the NAS of Ukraine are presented. The system is intended for automated monitoring and diagnostics of the condition of electrical equipment and parameters of its operation modes. Ultimately, the system enables enhancing the reliability of Ukrzaliznytsia (UZ) power supply systems and, consequently, the efficiency of railroad traffic management.